1968
DOI: 10.1139/z68-063
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion, intestinal absorption, and elimination of seawater and salts in the southern flounder, Paralichthys lethostigma

Abstract: Simultaneous measurements of flow rates and major electrolyte composition of urine and rectal fluid were made on five southern flounders, Paralichthys lethostigma, averaging 1,19 kg body weight. Rectal fluid is a residue of seawater swallowed by the fish, isosmotic to the blood plasma (336 mosmoles/l), and composed principally of magnesium (average 180 mmoles/l), sulfate (average 105 mmoles/l), and chloride (average 126 mmoles/l). Only 15.5% of the magnesium and 11.3% of the sulfate swallowed was absorbed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(79 citation statements)
references
References 1 publication
5
73
0
1
Order By: Relevance
“…Despite the importance of SO 4 2Ϫ regulation, the research on ion regulation has focused mainly on monovalent ions (Na ϩ and Cl Ϫ for osmoregulation and H ϩ and HCO 3 Ϫ for pH regulation) and divalent cations (Ca 2ϩ and Mg 2ϩ for regulation of muscular contraction and others). (6,21), but obligatory influx of SO 4 2Ϫ was nullified by excretion via the kidney in marine teleosts (3,7,8,28). We recently showed that the eel is unique in SO 4 2Ϫ regulation compared with other euryhaline teleosts because it has much higher plasma SO 4 2Ϫ in FW (ϳ6 mM) than in SW (ϳ1 mM) (35) as reported previously (23).…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Despite the importance of SO 4 2Ϫ regulation, the research on ion regulation has focused mainly on monovalent ions (Na ϩ and Cl Ϫ for osmoregulation and H ϩ and HCO 3 Ϫ for pH regulation) and divalent cations (Ca 2ϩ and Mg 2ϩ for regulation of muscular contraction and others). (6,21), but obligatory influx of SO 4 2Ϫ was nullified by excretion via the kidney in marine teleosts (3,7,8,28). We recently showed that the eel is unique in SO 4 2Ϫ regulation compared with other euryhaline teleosts because it has much higher plasma SO 4 2Ϫ in FW (ϳ6 mM) than in SW (ϳ1 mM) (35) as reported previously (23).…”
mentioning
confidence: 66%
“…Mg 2ϩ is the second most abundant cation in SW (ϳ50 mM) that is actively excreted by the kidney of marine teleosts (7,8). Because of the huge difference in Mg 2ϩ concentration between plasma and SW, Mg 2ϩ regulation at the kidney is also thought to be altered by the environmental salinity in fishes (2,4).…”
Section: Ncc Responsible For CL ϫ Uptake From the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the proportion of the calcium taken up from water in the intestine of seawater fish is very variable. For example, the cod (Gadus morhua) absorbs about 30% of the calcium from drinking water (Sundell et al 1993), while the flounder (Paralichthys lethostigma) absorbs about 70% (Hickman 1968). In tilapia (Oreochromis mossambicus), it has been shown that the net calcium transport in the intestine of seawater-adapted fish is significantly lower than in their freshwater counterparts, in which the uptake of calcium by the intestine represents a high proportion of whole body calcium uptake (Schoenmakers et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Water absorption by the intestine generates a high [SO 4 2Ϫ ] in the intestinal lumen (50-100 mM), and the steep concentration gradient promotes passive SO 4 2Ϫ absorption across the intestinal mucosa (34,60,62). Although passive SO 4 2Ϫ absorption dominates, an active secretory flux driven by an electroneutral brush-border SO 4 2Ϫ /Cl Ϫ exchanger is also present (62).…”
Section: ϫmentioning
confidence: 99%